2022
DOI: 10.3892/mmr.2022.12638
|View full text |Cite
|
Sign up to set email alerts
|

Ophiopogonin‑B targets PTP1B to inhibit the malignant progression of hepatocellular carcinoma by regulating the PI3K/AKT and AMPK signaling pathways

Abstract: ophiopogonin-B (oP-B) is a bioactive component from the root of Ophiopogon japonicus, which can exert anticancer effects on multiple malignant tumors. The present study aimed to uncover the effects of oP-B on hepatocellular carcinoma (Hcc) and the underlying mechanisms. an Hcc-xenografted mouse model was established and subsequently treated with oP-B (15 and 75 mg/kg) to observe the effects of oP-B on Hcc progression and protein tyrosine phosphatase 1B (PTP1B) expression in vivo. The Hcc cell line MHcc97-H was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…Ophiopogon in B (OP-B) is extracted from Radix Ophiopogon japonicus and has been reported to exert anticancer effects on different types of cancer, such as nasopharyngeal carcinoma (Dong et al, 2021), hepatocellular carcinoma (Yuan et al, 2022), lung cancer (Cheng et al, 2022). Previous findings have shown that OP-B has anticancer effects through the noniron ferroptosis pathway (Chen et al, 2016;Zhang et al, 2022).…”
Section: Ophiopogon In B (Op-b)mentioning
confidence: 99%
“…Ophiopogon in B (OP-B) is extracted from Radix Ophiopogon japonicus and has been reported to exert anticancer effects on different types of cancer, such as nasopharyngeal carcinoma (Dong et al, 2021), hepatocellular carcinoma (Yuan et al, 2022), lung cancer (Cheng et al, 2022). Previous findings have shown that OP-B has anticancer effects through the noniron ferroptosis pathway (Chen et al, 2016;Zhang et al, 2022).…”
Section: Ophiopogon In B (Op-b)mentioning
confidence: 99%
“…Specifically, Pituitary homeobox 1 (PITX1) exerts a tumor suppressive effect in hepatocarcinogenesis through regulation of Ras guanosine triphosphatase-activating protein (p120RasGAP) expression levels, but PTPN1 attenuates the protein stability of PITX by directly dephosphorylating PITX1 at residues Y160, Y175 and Y179 ( 144 ). Furthermore, down-regulation of PTPN1 expression inhibits HCC progression possibly by inactivating the PI3K/AKT pathway and activating the AMPK pathway ( 145 ).…”
Section: Dual Role Of Ptpns In Specific Cancersmentioning
confidence: 99%